Early Marriage as A Barrier to The Career and Educational Opportunity for The Youth in Georgia (Journal of Advanced Research in Social Sciences, 2018)
Early marriage is an official or unofficial relationship between two people when at least one of them is less than 18 years old. Various factors have an impact on early marriage such as traditions, norms, gender inequality, financial status, an attempt to avoid loneliness – especially in families where parents are divorced, or adolescents have family duties. The survey aims to study the effect of early marriage on education and the career opportunity of adolescents. The survey was conducted with 45 respondents (28 women and 17 men). The findings show that early marriage is a barrier to education, which later reduces employment opportunists as well. Adolescents have positive attitudes towards education, but only 1/5 of them were able to continue their studies after marriage. About 85% of adolescents do not have a job, but they receive essential financial and psychological support from their parents. The majority of respondents do not have any specific plans to continue their studies. However, they hope that in the future they will be able to get an education and be employed. One of the crucial factors for preventing early marriage is raising awareness of adolescents, their parents, families, and society about issues such as risks of early marriage, family planning, etc. Besides, it is impotent to provide information and services to adolescents to support their participation in education, improve their employability opportunities and social integration.